2018
DOI: 10.2344/anpr-66-01-02
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Tachycardia Due to Submucosal Migration of an Epinephrine-Soaked Swab During Nasal Intubation

Abstract: A 23-year-old healthy man was scheduled for extraction of his mandibular third molars under general anesthesia with nasotracheal intubation. Sudden sinus tachycardia up to 170 beats/min occurred when applying an epinephrine solution-soaked swab into the nasal cavity for preventing epistaxis during intubation. This was presumably evoked by submucosal migration of the swab into a false passage created because of the force applied during a prior failed attempt at nasal passage of the tracheal tube, and rapid epin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It has also been reported that the use of E for the prevention of nasal bleeding usually has a minimal effect on circulation in many patients [22,23]. However, sudden tachycardia was reported when E was used to prevent nasal bleeding [14]. In that study, it was assumed that severe tachycardia was triggered by submucosal migration of an epinephrine-soaked swab.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been reported that the use of E for the prevention of nasal bleeding usually has a minimal effect on circulation in many patients [22,23]. However, sudden tachycardia was reported when E was used to prevent nasal bleeding [14]. In that study, it was assumed that severe tachycardia was triggered by submucosal migration of an epinephrine-soaked swab.…”
Section: Discussionmentioning
confidence: 98%
“…Considering their signi cant use in medical procedures for > 60 years, their e cacy and side effects are well known. Although arrhythmia has been reported in literature for nasal treatments performed with E [14], no previous reports compared the vasoconstriction effects and safety of these two vasoconstrictors during NTI. This study aimed to determine whether E or T is more effective and safe for reducing nasal bleeding during NTI.…”
Section: Introductionmentioning
confidence: 99%
“…42 Accordingly, in difficult airway scenarios, avoidance of nasal bleeding is warranted when the nasal route is chosen for tracheal intubation. Although thermosoftening of ETTs 43 and the use of topical vasoconstrictors 44 are effective measures to decrease the risk of epistaxis, the facts that both strategies are time-consuming and are not used without risk 45 render them impractical in emergency airway management. Our findings of lower risks of both severe epistaxis regardless of the tracheal intubation approach and difficult airway manipulation associated with PFT tube use may further support its application in difficult airway management.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the use of E for the prevention of nasal bleeding usually has a minimal effect on circulation in many patients [ 25 , 26 ]. However, sudden tachycardia was reported when E was used to prevent nasal bleeding [ 16 ]. In that study, it was assumed that severe tachycardia was triggered by submucosal migration of an epinephrine-soaked swab.…”
Section: Discussionmentioning
confidence: 99%
“…Considering their significant use in medical procedures for >60 years, their efficacy and side effects are well known. Although arrhythmia and cardiac arrest have been reported in literature for nasal treatments performed with E and oxymetazoline [ 16 , 17 ] so far, no previous reports compared the vasoconstriction effects and safety of vasoconstrictors during NTI. This study aimed to determine whether E or T is more effective and safe for reducing nasal bleeding during NTI.…”
Section: Introductionmentioning
confidence: 99%